Solid-state magnetic traps and lattices - Knoerzer, J.; Schuetz, M. J. A.; Giedke, Geza; Huebl, Hans; Weiler, Mathias; Lukin, M. D.; Cirac, J. Ignacio (Physical Review B, 2018)
We propose and analyze magnetic traps and lattices for electrons in semiconductors. We provide a general theoretical framework and show that thermally stable traps can be generated by magnetically driving the particle's internal spin transition, akin to optical dipole traps for ultracold atoms. Next we discuss in detail periodic arrays of magnetic traps, i.e., magnetic lattices, as a platform for quantum simulation of exotic Hubbard models, with lattice parameters that can be tuned in real time. Our scheme can be readily implemented in state-of-the-art experiments, as we particularize for two specific setups, one based on a superconducting circuit and another one based on surface acoustic waves.
CRIS-Team Scopus Importer:2023-03-27